(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s ((3HcQ Hf eUWai GdQhejs)
(3ChdgG (B:s
(3ShQI eQje ecjI EdG BjI GdSLOI hgj KeGf Ch JSY hJSYhf BjI HSe Gddg GdQMef GdQMje cgjYU CeGd CHh YeQh GdgGAs
(3BNQgG (B:s
(3ShQI GdeQSdGJ (B: (3aHCj MOjK HYO gPG GdbQBf jDefhf EPG de jDefhG Hg hgh eYLR aj PGJg eTJed Ydi GdMLL GdhGVMI hGdeYGfj GdTQjaIbGd GdfHj (S0(3ef bQC ShQI hGdeQSdGJ cJH dg Cfg djS ef GdeTQcjf(S1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 110s
(3eYLe GdeDdajf (B2 / 266s
(3cTa GdXfhf (B1 / 186s
(3TPQGJ GdPgH (B5 / 392s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs